2013
DOI: 10.12724/ajss.25.1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Psychosocial Rehabilitation Facilities for Homeless Mentally Ill in India

Abstract: Homelessness due to chronic mental illness has become a major burden for most of the resource poor countries. The Kerala State in India has witnessed the efforts from the faith based organizations and religiously oriented families in the care and rehabilitation of the homeless mentally ill. This paper explores the processes used by these facilities for the care and rehabilitation of homeless mentally ill. Data were collected from the chief functionary of rehabilitation facilities, persons with mental illness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Forty percent of the residents in this study were brought in with the help of police/volunteers. The same pattern is noted in other studies: in non-governmental psychosocial rehab facilities, the majority of admissions were by police and social agencies/public (Anish, 2013) and among long-stay patients in mental hospitals, 55.4% were referred by police or magistrates ‘indicating a possible history of homelessness’ (Lakshmi Narasimhan et al, 2019). However, in the case of ‘governmental welfare homes’ residents were admitted as transferred from ‘mental hospital’ (Ravindren & Kurian, 2021).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Forty percent of the residents in this study were brought in with the help of police/volunteers. The same pattern is noted in other studies: in non-governmental psychosocial rehab facilities, the majority of admissions were by police and social agencies/public (Anish, 2013) and among long-stay patients in mental hospitals, 55.4% were referred by police or magistrates ‘indicating a possible history of homelessness’ (Lakshmi Narasimhan et al, 2019). However, in the case of ‘governmental welfare homes’ residents were admitted as transferred from ‘mental hospital’ (Ravindren & Kurian, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…However, the pattern noted in centres in another study showed a differing picture, with 71% having moderate disability and levels of functioning low in dimensions of community living and interpersonal relationship (Anish, 2013). Mild to moderate levels of disability is reported in 85% of residents of government welfare home and in 77.4% of long-stay patients in mental hospitals (Lakshmi Narasimhan et al, 2019; Ravindren & Kurian, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the clubhouse model for psychosocial rehabilitation was reported in China (Chen et al, 2020 ), one case describing linkages with a supported employment programme in surrounding communities (World Health Organization, 2021 ). Supported housing, especially focusing on those experiencing poverty and homelessness, was described in India, (Anish, 2013 ; Padmakar et al, 2020 ; World Health Organization, 2021 ) and Brazil (Acebal et al, 2021 ). In some instances, mental health teams performed various services, for instance facilitating residential training and placement according to individual preferences and needs – an example is a Recovery Oriented Services (ROSeS) team in India facilitating placement at a rural development centre for an individual who was interested in agriculture and animal husbandry (Vijayan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study from Kerala had observed that centers had one room per 13 residents and one toilet per 12 residents. 26 The formal rules for psychosocial rehab homes also categorically say that each dormitory can accommodate 25 inmates. Each person can get a living space of 60 square feet, and there shall be one bathroom and one toilet for every eight male and six female inmates.…”
Section: Nature Of the Centers Home Versus Hostelmentioning
confidence: 99%